MULTIMODAL SEMIOTIC SYSTEM ANALYSIS ON ADVERTISING AZAN SHOLAT (Malaysia Version) - Apriliyanti Apriliyanti (Journal MELT (Medium for English Language Teaching), 2019)
This research analized the multimodal of advertisement Azan Prayer Malaysia Version. Advertising both print media ads and electronic media ads is one text that has complexity of meaning. The complexity of the meaning that occurs because to convey the message in the ad not only used elements of language but also elements of nonverbal language and other visual means. Therefore, to understand the complexity of meaning needs to be done multimodal analysis in the ad. The multimodal analysis discussed in this study uses functional systemic linguistic theory (LSF). Multimodal model of analysis was developed from a combination of multimodal theory (Anstey & Bull, 2010), and multimodal analysis by Kress and Van Leeuwen (1996-2006). From the analysis of the advertisement Azan Prayer Malaysia Version obtained that this ad has multimodal semiotic system which includes linguistic, visual, audio, gestural, and spastial elements.